2013
DOI: 10.1590/s2176-94512013000500009
|View full text |Cite
|
Sign up to set email alerts
|

Effects of mandibular protraction appliance associated to fixed appliance in adults

Abstract: The effects of treating Class II malocclusion adult patients, by means of using Mandibular Protraction Appliance (MPA) combined with a fixed appliance were mostly observed in the mandibular arch, and consisted of buccal inclination, protrusion and intrusion of incisors, and mesialization and extrusion of the molars.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 27 publications
2
12
1
1
Order By: Relevance
“…Within the field of dentoskeletal relationships, it was important to note that there was no significant restriction of maxillary molar mesialization. This was also be observed in other studies that showed the improvement in Class II would occur to a larger extent by mesialization of the mandibular molar 9,13 and mild limitation of anterior displacement of the maxillary first molars 9,13 . According to the methodology used, there was significant restriction of maxillary anterior displacement, a restriction that was also highlighted in another study 25 . However, in a comparative study between MPA, Jasper Jumper and a Class II control group, there was no significant restriction of anterior maxillary growth in comparison with the control group 19 , and the same result was found in another study 24 .…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…Within the field of dentoskeletal relationships, it was important to note that there was no significant restriction of maxillary molar mesialization. This was also be observed in other studies that showed the improvement in Class II would occur to a larger extent by mesialization of the mandibular molar 9,13 and mild limitation of anterior displacement of the maxillary first molars 9,13 . According to the methodology used, there was significant restriction of maxillary anterior displacement, a restriction that was also highlighted in another study 25 . However, in a comparative study between MPA, Jasper Jumper and a Class II control group, there was no significant restriction of anterior maxillary growth in comparison with the control group 19 , and the same result was found in another study 24 .…”
Section: Discussionsupporting
confidence: 82%
“…The MPA improved the molar ratio and increased the interincisive angle, which could be explained by lingualization of the maxillary incisors 10,25 and vestibularization of the mandibular incisors 13,24 . According to the original proposal of the MPA, the main concern related to mandibular advancement was to maintain the inclination of the mandibular incisors 11,12 .…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…Despite MPA's widespread use in South America, there are only a few reports on its effects (5,8,9) at different stages of dentofacial development. Furthermore, these reports do not identify changes caused by MPA according to dentofacial development, an important variable associated with craniofacial changes produced by orthopedic appliances (1).…”
Section: Introductionmentioning
confidence: 99%